2018
DOI: 10.1111/jeu.12496
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Tintinnopsis everta Kofoid and Campbell 1929 (Alveolata, Ciliophora, Tintinnina) Based on Taxonomic and Genetic Analyses—Discovery of a New Complex Ciliary Pattern

Abstract: The about 1,000 species of tintinnid ciliates are identified and classified almost exclusively based on their lorica features, although the shortcomings of this structure are well‐known, e.g. causing uncertain species limitations and nonmonophyletic taxa. Hence, the present redescription of Tintinnopsis everta Kofoid and Campbell, 1929 considers not only the lorica characteristics, but focuses on cell and genetic features. The species is redescribed from the North Atlantic and adjacent sea areas, namely the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…Based on ITS1-5.8S-ITS2, a sequence previously obtained for this species in Qingdao, China (KU715813; [48]) groups with our sequence, and both are 96.2% similar. Tintinnopsis kiaochowensis forms a fully-supported clade with T. everta (MG461220; [33]) based on SSU rDNA, and both sequences are 99.0% similar. The newly sequenced population of T. uruguayensis forms a fully-supported clade with the North-Atlantic population of the same species, based on both SSU rDNA and LSU rDNA (JN831838 and JN831923; [25]); the two populations are 100% identical in both markers.…”
Section: Sequence Comparison and Phylogenetic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on ITS1-5.8S-ITS2, a sequence previously obtained for this species in Qingdao, China (KU715813; [48]) groups with our sequence, and both are 96.2% similar. Tintinnopsis kiaochowensis forms a fully-supported clade with T. everta (MG461220; [33]) based on SSU rDNA, and both sequences are 99.0% similar. The newly sequenced population of T. uruguayensis forms a fully-supported clade with the North-Atlantic population of the same species, based on both SSU rDNA and LSU rDNA (JN831838 and JN831923; [25]); the two populations are 100% identical in both markers.…”
Section: Sequence Comparison and Phylogenetic Analysesmentioning
confidence: 99%
“…Thus, we applied common criteria to verify that eld-isolated specimens were not confounded with other species (e.g. as done by Gruber et al [33]): the three species were distinguished by careful evaluation of their morphological features and lorica size in vivo, and the absence of potentially confounding, cooccurring species was con rmed with further analyses of loricae and protargol-stained cells. For each species, a single specimen was isolated at 400× magni cation, washed ve times with 0.22-μm ltered sample water, and used for DNA extraction with the DNeasy Blood & Tissue kit (Qiagen).…”
Section: Dna Extraction Pcr Ampli Cation and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent researches have revealed that a combination of both molecular and classic morphological data is indispensable for studying the diversity, taxonomy, phylogeny and biogeography of tintinnines [21][22][23][24][25][26][27][28]. Unfortunately, SSU rRNA gene sequences and cytological data, including details of the ciliature, are available for only 10 and 5 % of nominal morphospecies, respectively [18,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Jörgensen, 1924 are characterized by having a broadly obovate bowl with densely agglomerated particles and a cylindrical, hyaline collar that may be either spiraled or annular.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the current lorica-based taxonomy does not allow estimating tintinnine diversity accurately, and it does not provide a natural classi cation. Accordingly, several studies have incorporated more informative characters, namely, cytological and/ or molecular data, in tintinnine systematics (e.g., [27] [28] [29] [30] [31] [32] [33] [34] [35] [36]). Still, cell characters and DNA sequences are only known for about 3% and 10% of the described tintinnine morphospecies, respectively (e.g., [22] [37]), and considerable efforts are needed to increase the availability of these types of information.…”
Section: Introductionmentioning
confidence: 99%